Analytical Method Validation of Selected Organochlorine Pesticides in Fortified Rice Using Gas Chromatography with Electron Capture Detector - Wardani, Mutia Kusuma; Sutriyanto, Bambang; Lukitaningsih, Endang; Rohman, Abdul (Fakultas Farmasi, Universitas Gadjah Mada, 2014)
Gas chromatography with electron capture detector (GC-ECD) has been validated for simultaneous determination of selected organochlorine pesticides namely heptachlor, endosulfan, dieldrin, dan p,p’-dichlorodiphenyltrichloroethane (p,p’-DDT) using aldrin as standard internal. Some parameters for analytical method validation were evaluated, i.e. linearity, precision, sensitivity expressed with limit of detection and limit of quantification, and recovery. GC-ECD was linear for determination of these pesticides with r values ≥ 0.99. The values of LOD obtained were 2.50, 2.97, 1.61, and 2.54 ng/mL for heptachlor, endosulphan, dieldrin, and p,p’-DDT, respectively. Furthermore, the relative standard deviation (RSD) values obtained for the assessment of analytical precision were lower than those required by Horwitz. Finally, the used GC-ECD method was accurate for determination of these organochlorine psticides in fortified rice samples which were indicated by the acceptable recovery percentages.